Social, biological, psychological, economic and cultural contexts of people with wounded legs (2010)
This research characterizes the cultural, economic, social, biological and psychological context of users of the Injury Treatment Center program led by a group of lecturers of the area of Groundwork in Nursing of the Nursery Faculty of Colombia's National University. It is well known that the care of injured people demands the knowledge of the severity thereof, especially vascular injuries that are chronic and heal slowly. The conditions delaying the recovery from these injuries imply a high level of complication, as well as the individual's nutritional state, access to medical assistance and motivation to recover. The poor healing and injuries derived from slow recovery processes of the skin integrity in injuries of vascular origin are a serious health problem because they expose the individual to infections that may become severe and even fatal, also because they cause an important alteration of the self-esteem, which in turn can cause, in some people, isolation and disability feelings. In the process of recovery, one should take into account aspects such as nutrition, age, associated diseases, and the condition of the injury, physiological aspects and the social support provided to the person. Once the multiple causality is defined in the individuals with injuries of vascular origin, this research will be carried out, whose intention is to provide, from the different contexts of the study, the theoretical and practical bases that may orientate, in an assertive manner, the nursing professional and the rest of the interdisciplinary group for them to be able to prepare more integral care plans that go beyond the biological aspect in order to improve the health conditions among vulnerable population.